Ballistic resistance of high hardness armor steels against 7.62 mm armor piercing ammunition - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2013)
Although advanced lightweight composite based armors are available, high hardness steels in military vehicles are often used to provide ballistic protection at a relatively low cost and is an interesting material due to its widespread usage in vehicle structure. In this study, ballistic limit of 500 HB armor steel was determined against 7.62 mm 54R B32 API hardened steel core ammunition. Lagrange and smoothed particle hydrodynamics (SPH) simulations were carried out using 3D model of bullet and high hardness armor target. Perforation tests on 9 and 20 mm thickness armor were performed to validate simulation methodology. Also material tests were performed for armor steel and ammunition hardened steel core to develop Johnson-Cook constitutive relations for both strength and failure models. Finally, results from 3D numerical simulations with detailed models of bullet and target were compared with experiments. The study indicates that the ballistic limit can be quantitatively well predicted independent of chosen simulation methodology, but qualitatively some differences are seen during perforation and fragmentation. As shown in results, good agreement between Ls-Dyna simulations and experimental data was achieved by Lagrange formulation with the full bullet model. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ballistics; High hardness steel; Armor piercing bullet; Smoothed particle hydrodynamics; Lagrange; Numerical simulation; IMPACT; PROJECTILE; PENETRATION; SIMULATION